A Comparison of Butterfly Diversity Results between iNaturalist and Expert Surveys in Eastern Oklahoma - Alexander J. Harman; Madeline M. Eori; W. Wyatt Hoback (Diversity)
Ongoing worldwide biodiversity declines and range shifts associated with climate change increase the importance of documenting the current distributions of species to establish baseline data. However, financial and logistical constraints make it impossible for taxonomic experts to conduct thorough surveys in most locations. One popular approach to offset the lack of expert sampling is using community science data collected by the public, curated, and made available for research. These datasets, however, contain different biases than those typically present in data collected through conventional survey practices, often leading to different results. Recent studies have used massive datasets generated over large areas; however, less is known about the results obtained at smaller scales or with more limited sampling intervals. We compared butterfly observations in eastern Oklahoma using a dataset obtained from the popular community science website iNaturalist and one collected during targeted surveys of glade habitats conducted by taxonomic experts. At the county-level scale, the relative abundances of butterfly species correlated well between the glade surveys and the iNaturalist observations, and there was no difference in the relative abundance of different butterfly families between the two survey methods. However, as anticipated, the conventional surveys outperformed the community science data in measuring biodiversity at a smaller geographic scale.